Precise Selection Techniques for Multi-Touch Screens - Benko, Hrvoje; Wilson, Andy; Baudisch, Patrick (CHI '06 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2006)
The size of human fingers and the lack of sensing precision can make precise touch screen interactions difficult. We present a set of five techniques, called Dual Finger Selections, which leverage the recent development of multitouch sensitive displays to help users select very small targets. These techniques facilitate pixel-accurate targeting by adjusting the control-display ratio with a secondary finger while the primary finger controls the movement of the cursor. We also contribute a “clicking” technique, called SimPress, which reduces motion errors during clicking and allows us to simulate a hover state on devices unable to sense proximity. We implemented our techniques on a multi-touch tabletop prototype that offers computer visionbased tracking. In our formal user study, we tested the performance of our three most promising techniques (Stretch, X-Menu, and Slider) against our baseline (Offset), on four target sizes and three input noise levels. All three chosen techniques outperformed the control technique in terms of error rate reduction and were preferred by our participants, with Stretch being the overall performance and preference winner.